A Prospective Multicenter Study Evaluating Endoscopy Competence Among Gastroenterology Trainees in the Era of the Next Accreditation System. (February 2020) - Han, Samuel; Obuch, Joshua C.; Duloy, Anna M.; Keswani, Rajesh N.; Hall, Matt; Simon, Violette; Ezekwe, Eze; Menard-Katcher, Paul; Patel, Swati G.; Aagard, Eva; Brimhall, Bryan; Ahmad, Asyia; et al.
Abstract : Purpose: The Next Accreditation System requires training programs to demonstrate competence among trainees. Within gastroenterology (GI), there are limited data describing learning curves and structured assessment of competence in esophagogastroduodenoscopy (EGD) and colonoscopy. In this study, the authors aimed to demonstrate the feasibility of a centralized feedback system to assess endoscopy learning curves among GI trainees in EGD and colonoscopy. Method: During academic year 2016–2017, the authors performed a prospective multicenter cohort study, inviting participants from multiple GI training programs. Trainee technical and cognitive skills were assessed using a validated competence assessment tool. An integrated, comprehensive data collection and reporting system was created to apply cumulative sum analysis to generate learning curves that were shared with program directors and trainees on a quarterly basis. Results: Out of 183 fellowships invited, 129 trainees from 12 GI fellowships participated, with an overall trainee participation rate of 72.1% (93/129); the highest participation level was among first-year trainees (90.9%; 80/88), and the lowest was among third-year trainees (51.2%; 27/53). In all, 1, 385 EGDs and 1, 293 colonoscopies were assessed. On aggregate learning curve analysis, third-year trainees achieved competence in overall technical and cognitive skills, while first- and second-year trainees demonstrated the need for ongoing supervision and training in the majority of technical and cognitive skills. Conclusions: This study demonstrated the feasibility of using a centralized feedback system for the evaluation and documentation of trainee performance in EGD and colonoscopy. Furthermore, third-year trainees achieved competence in both endoscopic procedures, validating the effectiveness of current training programs. Abstract : Supplemental Digital Content is available in the text.